2003
DOI: 10.1089/104454603322163844
|View full text |Cite
|
Sign up to set email alerts
|

Response to Methylphenidate in Children with Attention Deficit Hyperactivity Disorder and Manic Symptoms in the Multimodal Treatment Study of Children with Attention Deficit Hyperactivity Disorder Titration Trial

Abstract: Objective:Recent reports raise concern that children with attention deficit hyperactivity disorder (ADHD) and some manic symptoms may worsen with stimulant treatment. This study examines the response to methylphenidate in such children. Methods:Data from children participating in the 1-month methylphenidate titration trial of the Multimodal Treatment Study of Children with ADHD were reanalyzed by dividing the sample into children with and without some manic symptoms. Two "mania proxies" were constructed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 38 publications
6
80
1
3
Order By: Relevance
“…109 Galanter and colleagues examined the response to MPH in children with ADHD and some manic symptoms. 112 Their findings suggested that these children respond robustly to MPH during the first month of treatment and that they are not more likely to have an adverse response to MPH. 112 In 2004, the authors of the MTA trial published results of a follow-up 10 months beyond the 14 months of intensive intervention.…”
Section: Results Of the Mta Trialmentioning
confidence: 99%
See 3 more Smart Citations
“…109 Galanter and colleagues examined the response to MPH in children with ADHD and some manic symptoms. 112 Their findings suggested that these children respond robustly to MPH during the first month of treatment and that they are not more likely to have an adverse response to MPH. 112 In 2004, the authors of the MTA trial published results of a follow-up 10 months beyond the 14 months of intensive intervention.…”
Section: Results Of the Mta Trialmentioning
confidence: 99%
“…112 Their findings suggested that these children respond robustly to MPH during the first month of treatment and that they are not more likely to have an adverse response to MPH. 112 In 2004, the authors of the MTA trial published results of a follow-up 10 months beyond the 14 months of intensive intervention. 113 Of the 579 children who entered the study, 540 (93%) participated in this first follow-up.…”
Section: Results Of the Mta Trialmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that psychoeducation and family involvement (which may in certain cases require targeted specific family interventions 34,35 ) are essential components of our approach. Below we describe some of the evidence that is emerging for targeting mood regulation in CBT and how it is used in our clinic.…”
Section: How To Deal With Mood Regulation Problemsmentioning
confidence: 99%